The hospital accreditation process as a tool for quality management: how does it happen? (Research, Society and Development, 2023)
Introduction: The Accreditation process is linked to the idea of ​​preserving and valuing the quality of life, as it is a quality assessment procedure that stipulates minimum standards to ensure customer satisfaction. Therefore, according to the National Accreditation Organization (ONA), Accreditation is defined as a system for evaluating and certifying the quality of health services. Objective: to discuss the development of the hospital accreditation process through the elucidation of the main types, such as evaluation methods, as well as specific principles. Methodology: Study of the integrative literature review type, carried out between July and November 2022, in the Virtual Health Library (VHL), with the descriptors "Accreditation", "Hospital Accreditation", "Quality of Care", associated by the Boolean operator " AND”, and selected from the full and available text filters, documents like scientific articles; year of publication 2012 to 2022. The research population included 22 documents; later, a critical and reflective reading was carried out and, thus, the sample of 07 articles was established. Results and Discussion: The objective is to promote a constant process of evaluation and improvement in health services and, in this way, improve the quality of care in the country. Certifying Health Service Provider Organizations; Dental Services; Health and Risk Prevention Programs; Health Services. Mission to improve the management, quality and safety of assistance in the Health Sector, through the Brazilian Accreditation System. And with the Vision of making the ONA Accreditation recognized by Brazilian society as a synonym of safety, quality and credibility in the Health Sector. Conclusion: The Accreditation Process aims to improve care, so that it becomes more humanized for the health of human beings who seek hospitals in need of care and support. Hospital Service Provider Organizations need to go through this Process to receive certification, to guarantee patients that they have quality care. And for that, the Ministry of Health, in partnership with the National Accreditation Organization, launched the Brazilian Manual of Hospital Accreditation, to serve as a basis and support throughout the evaluation of the Accrediting Institution.